LRH1 Acts as an Oncogenic Driver in Human Osteosarcoma and Pan-Cancer - Song, Yang; An, Weiwei; Wang, Hongmei; Gao, Yuanren; Han, Jihua; Hao, Chenguang; Chen, Lin; Liu, Shilong; Xing, Ying (Frontiers in Cell and Developmental Biology, 2021)
Osteosarcoma (OS), which mainly occurs during childhood and adolescence, is a devastating disease with poor prognosis presented by extreme metastases. Liver receptor homolog 1 (LRH1) is upregulated and plays a vital role in the metastasis of some malignancies, but the role of LRH1 in the metastasis of OS is unknown. By immunohistochemistry (IHC), we demonstrated that LRH1 expression was significantly higher in tumour tissues than in normal bone tissues. High LRH1 expression was associated with poor differentiation and advanced TNM stage in OS patients. Gene Ontology (GO) enrichment analyses based on high-throughput RNA‑seq data revealed that LRH1 played a pivotal role in the positive regulation of cell migration and motility and angiogenesis. Consistently, LRH1 deletion attenuated the migration of human OS cells, concurrent with the upregulation of epithelial markers and downregulation of mesenchymal markers. In addition, shRNAs targeting LRH1 inactivated the TGFβ signalling pathway. LRH1 knockdown inhibited human umbilical vein endothelial cell (HUVEC) proliferation and tube formation. After LRH1 knockdown, vascular endothelial growth factor A (VEGFA) expression was downregulated. Based on The Cancer Genome Atlas (TCGA) database, high LRH1 expression predicts poor survival in lung squamous cell carcinoma (LUSC), kidney renal papillary cell carcinoma (KIRP) and pancreatic adenocarcinoma (PAAD). Using multiomic bioinformatics, a positive correlation between LRH1 and EMT-related genes was found across these three cancer types. GO analysis showed that LRH1 and its coexpressed genes were associated with “positive regulation of cell migration” “blood vessel morphogenesis” and “vasculogenesis” in LUSC and/or KIRP. Downregulation of LRH1 significantly hindered the migration and motility of LUSC cells. Our results indicate that LRH1 plays a tumour-promoting role in human OS and that LRH1 can predict metastatic potential early and may serve as a potential target for cancer therapy.